Intermediate microRNA expression profile in Graves' disease falls between that of normal thyroid tissue and papillary thyroid carcinoma. Issue 1 (1st July 2016) - Pohl, Matthias; Grabellus, Florian; Worm, Karl; Arnold, Georg; Walz, Martin; Schmid, Kurt Werner; Sheu-Grabellus, Sien-Yi
Abstract : Aims: Many studies have previously reported a higher prevalence of papillary thyroid carcinomas (PTC) in patients with Graves' disease (GD). MicroRNAs (miRNAs) are small, non-coding RNAs that are upregulated in PTC compared with benign thyroid tissue. The objective of the study was to examine the miRNA expression of selected miRNAs that are known to be upregulated in PTC in patients with GD. Methods: Paraffin embedded thyroid tissue from 159 patients with GD was screened for expression of the miRNAs 146b, 181b, 21, 221 and 222 by RT-PCR. The expression profiles of four normal thyroids, 50 PTCs without concomitant GD and 11 patients with untreated GD served as the controls. Results: The expression pattern of these miRNAs in patients with GD is intermediate between that of benign thyroid tissue (p<0.001) and PTC (in three out of five miRNAs, p<0.001). This corresponds to a 15-fold change for GD versus PTC, and a 31-fold change for GD versus normal thyroid tissue. The miRNA expression in 11 papillary microcarcinomas found in our study (a prevalence of 0.07) was not different from that in PTC samples from patients without GD for four of five miRNA types. Furthermore, we found a significant difference in the expression of miRNA 221/222 between treated and untreated GD tissue. Conclusions: In conclusion, we found an intermediate expression of specific miRNAs in thyroid tissue from patients with GD that fell between the expression levels found in normal thyroid glands and PTC, which suggests a possible influence of certain miRNAs on developing PTC in patients with GD.